Critical events an anthropological perspective on contemporary India - Das, Veena 1945- (Oxford Univ. Press, 1995)
The critical events that Professor Das analyses have all instituted new sorts of action, which have in turn redefined traditional categories such as codes of purity and honour, the meaning of martyrdom, and the construction of a heroic life. The author shows how these new forms took shape and were appropriated by a variety of political actors, such as caste groups, religious communities, women's groups, and the nation as a whole